Genome-Wide Identification and Expression Analysis of bHLH-MYC Family Genes from Mustard That May Be Important in Trichome Formation - Jianzhong Li; Guoliang Li; Caishuo Zhu; Shaoxing Wang; Shifan Zhang; Fei Li; Hui Zhang; Rifei Sun; Lingyun Yuan; Guohu Chen; Xiaoyan Tang; Chenggang Wang; et al. (Plants)
The trichomes of mustard leaves have significance due to their ability to combat unfavorable external conditions and enhance disease resistance. It was demonstrated that the MYB-bHLH-WD40 (MBW) ternary complex consists of MYB, basic Helix-Loop-Helix (bHLH), and WD40-repeat (WD40) family proteins and plays a key role in regulating trichome formation and density. The bHLH gene family, particularly the Myelocytomatosis (MYC) proteins that possess the structural bHLH domain (termed bHLH-MYC), are crucial to the formation and development of leaf trichomes in plants. bHLH constitutes one of the largest families of transcription factors in eukaryotes, of which MYC is a subfamily member. However, studies on bHLH-MYC transcription factors in mustard have yet to be reported. In this study, a total of 45 bHLH-MYC transcription factors were identified within the Brassica juncea genome, and a comprehensive series of bioinformatic analyses were conducted on their structures and properties: an examination of protein physicochemical properties, an exploration of conserved structural domains, an assessment of chromosomal positional distributions, an analysis of the conserved motifs, an evaluation of the gene structures, microsynteny analyses, three-dimensional structure prediction, and an analysis of sequence signatures. Finally, transcriptome analyses and a subcellular localization examination were performed. The results revealed that these transcription factors were unevenly distributed across 18 chromosomes, showing relatively consistent conserved motifs and gene structures and high homology. The final results of the transcriptome analysis and gene annotation showed a high degree of variability in the expression of bHLH-MYC transcription factors. Five genes that may be associated with trichome development (BjuVA09G22490, BjuVA09G13750, BjuVB04G14560, BjuVA05G24810, and BjuVA06G44820) were identified. The subcellular localization results indicated that the transcription and translation products of these five genes were expressed in the same organelle: the nucleus. This finding provides a basis for elucidating the roles of bHLH-MYC family members in plant growth and development, and the molecular mechanisms underlying trichome development in mustard leaves.